Distribution Characteristics of Refrigerant in Micro-channel Evaporator under Frosting Conditions - Sheng Wei; Lan Qingyun; Pei Yang; Ding Guoliang (Zhileng xuebao)
A refrigerant distribution parameter (RDP) evaluation method is proposed to investigate the influence of frost formation on the distribution of refrigerant in micro-channel evaporators. The distribution of refrigerant under frosting conditions was measured by infrared thermal imaging and digital image processing. Experimental results showed that with an increase in thickness of the surface frost layer of the evaporator, the overheating zone in the evaporator decreased gradually and the distribution of the refrigerant in the two-phase zone was more uniform. In a 180 min experiment conducted in this study, the refrigerant overheat area decreased by 22.7%, the RDP increased by 17.2%, and the heat exchange rate decreased by 2.34%. These results provide a quantitative method to examine the distribution characteristics of micro-channel evaporator refrigerant under frosting conditions.